2016
DOI: 10.3171/2015.6.jns15729
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive hemicraniectomy: predictors of functional outcome in patients with ischemic stroke

Abstract: P atients presenting with large ischemic strokes may develop uncontrollable, progressive brain edema that puts them at risk for compression of brain parenchyma and cerebral herniation. 23 There are a limited number of therapeutic options, but research has shown that operative procedures, such as decompressive hemicraniectomy (DH), decrease patient mortality.32 Malignant infarction treated only by conservative approaches results in a mortality rate of 80% within the 1st week of the stroke. 15Edema that does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 36 publications
1
41
0
9
Order By: Relevance
“…Studies demonstrated that having a stroke affecting the dominant hand might be associated with unfavourable functional outcomes at the acute stage. However, in subacute and chronic phases, it is suggested that there is no significant difference in functional improvement among individuals with dominant or non‐dominant paralyses post‐stroke (Lima et al, ; Nam et al, ; Daou et al, ). Using client‐centred tools such as Canadian occupational performance measure (COPM), individuals post‐stroke tend to setup rehabilitation goals influenced by their stroke severity more than their handedness (Waddell et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrated that having a stroke affecting the dominant hand might be associated with unfavourable functional outcomes at the acute stage. However, in subacute and chronic phases, it is suggested that there is no significant difference in functional improvement among individuals with dominant or non‐dominant paralyses post‐stroke (Lima et al, ; Nam et al, ; Daou et al, ). Using client‐centred tools such as Canadian occupational performance measure (COPM), individuals post‐stroke tend to setup rehabilitation goals influenced by their stroke severity more than their handedness (Waddell et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, no previous study has reported the prevalence of PAs in this population. Our findings should be cautiously compared with those from previous studies that almost uniquely included neurosurgical patients (4)(5)(6)(7)(8)(9). The prevalence of PAs may vary according to the quality of the pupillary evaluation, which can be challenging at the bedside (2,(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 58%
“…This is probably mainly due to the high price of this technology. However, the high frequency of clinical PAs we detected in our study may help to justify the purchase of [9] Data are expressed as number [%].…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese study evaluated the effectiveness of DC in patients over 80 years of age, concluding that DC, even in patients in this age group, may increase the survival rate without severe compromise of functionality 18 . In a recent American study, involving more than 1,600 patients, the authors reported the results according to age as uni-and multivariate analysis, not taking into account this variable as a significant predictor of clinical outcome 20 .…”
Section: Discussionmentioning
confidence: 99%